2023
DOI: 10.3389/ffgc.2023.1127601
|View full text |Cite
|
Sign up to set email alerts
|

Policy challenges for agroforestry implementation in Europe

Abstract: Agroforestry (AF) is a sustainable land use practice and system that increases the ecosystem services delivery from agricultural lands compared with treeless systems. Agroforestry can be considered a practice when linked to plot scale (silvoarable, silvopasture, homegarden, woody linear landscape strips, and forest farming), and a system when associated with the global farm scale. The enhancement of the ecosystem services is associated with the use and promotion of the biodiversity caused by the presence of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that certain agroforestry systems, like silvopasture, exhibit economic viability and generate profits. However, other practices such as biomass plantings or riparian buffers may require the establishment of markets that provide compensation for the ecosystem services, they offer in order to be financially feasible (Mosquera-Losada et al, 2023;Ntawuruhunga et al, 2023). Additionally, the process of social change and networking will also be influential as attitudes shift to embrace alternative approaches (Annosi et al, 2022).…”
Section: Agroforestry Adoption Challenges and Future Directions To Ov...mentioning
confidence: 99%
“…Previous studies have demonstrated that certain agroforestry systems, like silvopasture, exhibit economic viability and generate profits. However, other practices such as biomass plantings or riparian buffers may require the establishment of markets that provide compensation for the ecosystem services, they offer in order to be financially feasible (Mosquera-Losada et al, 2023;Ntawuruhunga et al, 2023). Additionally, the process of social change and networking will also be influential as attitudes shift to embrace alternative approaches (Annosi et al, 2022).…”
Section: Agroforestry Adoption Challenges and Future Directions To Ov...mentioning
confidence: 99%
“…Agroforestry can also be found in Europe [7]. The potential of agroforestry systems to provide economic, environmental, and social benefits in Europe has been demonstrated by national research programs and European Union research projects [7][8][9][10][11]. The function of agroforestry [12,13] can be expected because of the composition and arrangement of plant and tree species in one plot of land [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that AF systems are a sustainable land management option that delivers market and non-market goods and services and the increasing support from the CAP programs, governments need to develop policies and actions that foster agroforestry within an EU policy framework [19]. In addition, a European AF strategy is needed to provide a proper framework that is recognized by the member states, although, the implementation of such strategy would require knowledge of these types of practices at the European level [19].…”
Section: Introductionmentioning
confidence: 99%